Multiple sprints performance and fatigue level between Turkish national male senior free and Greco-Roman styles' wrestlers - Akif Ziyagil, M.; Türkmen, M. (Kinesiologia Slovenica, 2017)
Multiple sprints test (MST) is a useful tool for testing directly the efficiency of phosphagen system and indirectly the efficiency of MaxVO2 enhancing capacity to recover between sprints. The aim of this study is to compare the physical characteristics and multiple sprints performance and sprints induced fatigue level between male Turkish National Free Sytle Wrestlers (FSW) and Greco-Roman Styles Wrestlers (GSW). The data were collected from 25 FSW and 21 GSW at male senior level. Speed and reduction in speed level were tested by MST. A t-test was used for comparing two-groups. Also, correlations coefficients were calculated among variables. The results of this study showed that GSW were more explosive during the first 10 m part, while FSW were faster at the second 10 m part of each 20 meters sprint. No significant difference was observed between the two styles in the mean 20 m sprinting speed during MST. Sprints variables showed negative correlation with physical characteristics in two styles but level of wrestlers was only correlated with first 10 m sprint speed in GSW. The ability to resist anaerobic fatigue in GSW was higher than FSW during repeated sprints. In conclusion, the intensity, the number of intervals and duration of explosive exercises should be based on the scores of GSW and FSW depending on the demand of wrestling in MST.